Corrosion Inhibition Potential of Ethanol Extract of Bryophyllum pinnatum Leaves for Zinc in Acidic Medium - Kolo, Alhaji Modu; Idris, Sunusi; Bamishaiye, Oloyede Martins (Edelweiss Applied Science and Technology, 2018)
The inhibitive and adsorption properties of ethanol extract of Bryophyllum pinnatum leaves were studied using weight loss, potentiodynamic polarization, Scanning Electron Microscopy (SEM) and Fourier transformed infra-red spectroscopy (FTIR) methods of monitoring corrosion. The results obtained, indicated that ethanol extracts of Bryophyllum pinnatum leaves is a good adsorption inhibitor for the corrosion of zinc in sulphuric acid solutions. The adsorption of the inhibitor on zinc surface was found to be spontaneous and supported the Langmuir adsorption model. From the calculated values of free energy of adsorption, the activation energy and the variation of inhibition efficiency with temperature, a physical adsorption mechanism has been proposed for the adsorption of ethanol extract of Bryophyllum pinnatum leaves on zinc surface. Results from potentiodynamic polarization study indicated that Bryophyllum pinnatum is a mixed-type corrosion inhibitor. Analysis of spectra obtained from Fourier transformed infra-red spectrophotometer (FTIR) revealed that some functional groups presence in the spectra of the inhibitors were missing in the spectra of the corrosion products which also indicated that there is an interaction between zinc and the inhibitor.